Dinamika Kebijakan Penguasa Muslim atas Masyarakat Kristen di Timur Tengah: Studi Kasus era Daulah Umayyah dan Abbasiyah (Journal of Comparative Study of Religions, 2024)
This study aims to portray the state of the church and Christian society in the Middle East during the Umayyad and Abbasid eras using portraits from Christian sources. This is based on the fact that the narratives commonly found about Muslim-Christian relations during the Islamic state are dominated by history from the perspective of the rulers/conquerors, namely Muslims. This study is a literature study using primary references from literature originating from Christian communities in the Middle East. The results of this study show that the relationship between Muslims and Christians experienced dynamics and ups and downs. Although the various descriptions above are largely based on non-Muslim sources, in fact not all of them view Muslim-Christian relations negatively during the Umayyad and Abbasid dynasties. One thing that needs to be underlined is that the various policies of the rulers towards non-Muslims, especially Christians, were influenced by many things and did not have a single factor solely because of theological differences. Economic factors, political factors, and social factors are factors that are considered in the differences in policies towards Christian communities.